Media Politics and Public Opinion Formation in the 2024 East Java Gubernatorial Election: Implications for Voter Behavior - Intan, May Hesti Cahya; Martini, Rina (Lembaga Teewan Journal Solutions, 2026)
This study examines the role of media politics in shaping public opinion and voter behavior during the 2024 East Java Gubernatorial Election. In contemporary elections, media serves as a strategic arena where political actors construct narratives, influence public perceptions, and compete for voter attention. This research employs a qualitative descriptive approach using a literature study method. Data were collected from scholarly articles, books, official reports, and credible online media published during the election period, then analyzed through content analysis. The findings reveal that media significantly influences issue salience through agenda-setting, making topics such as regional development, public services, and governance performance dominant in public discourse. Framing practices also shape how voters interpret candidates’ competence, leadership, and credibility. Moreover, social media has become an essential platform for political communication by facilitating direct interaction between candidates and the public while simultaneously increasing information fragmentation and political polarization. The study further indicates that voter behavior is shaped by the interaction of media exposure, social environments, and individual interpretation. Although media does not directly determine voting decisions, it plays a crucial role in influencing cognitive evaluations and political preferences. Overall, the study concludes that media politics substantially contributes to public opinion formation and voter behavior in the 2024 East Java Gubernatorial Election through complex interactions with social and psychological factors.